Pengaruh Promosi, Harga, dan Kualitas Produk terhadap Keputusan Mahasiswa Mendaftar di STIE Gici Business School - Syamsiah, Dede Siti; Ekawati, Christina (SAFE-Network, 2023)
This study aims to analyze the effect of promotion, price, and product quality on students' decisions in choosing STIE GICI. The research sample consisted of 80 students. The data analysis method used is multiple linear regression. The results showed that the results of the simultaneous hypothesis testing of all variables consisting of promotion, price and product quality had a significant influence on the student's decision to choose STIE GICI. In addition, partial hypothesis testing also shows that all variables, namely promotion, price, and product quality, have a significant effect on the decision to choose STIE GICI. The findings of this study can assist STIE GICI in planning a more effective marketing strategy to increase the number of new student applicants. By paying attention to the aspects of promotion, price, and product quality, STIE GICI can attract more prospective students and increase their decision to choose the institution.